Incorporating Energy Cycle Externality Costs and Benefits in India's Power System Planning Mechanisms - Powell, Stephen (World Bank, Washington, DC, 2012)
The power sector in India plays a fundamental role in the economic development process. The country faces formidable challenges in meeting its energy needs in an environmentally sustainable manner and at reasonable costs. The planning and operation of the sector has hitherto been conducted without due regard to the environmental consequences. As a result, additions to capacity in recent years have been sub-optimal. Moreover different types of capacity are treated differently. Hydropower is required directly to bear more of its external environmental costs than other sources. The recent Supreme Court ruling has reinforced this tendency. Looking forward, much of the large capacity additions required over the next few years are likely to be coal-fired, with concomitant effects on the country's environment. Against that background, the paper looks at India's power generation planning process; whether and how it might adapt in the light of increased attention to environmental costs and benefits; and if there are other, better ways of internalizing environment externalities. It takes as its starting point the conclusions of the companion paper by Anil Markandya. These are that the external environmental costs of fossil fuel generation are as high or higher than estimates derived for developed countries; that estimates of the external costs of both fossil-fuelled and hydro for India should now be determined more precisely and used at the strategic level in planning, at the regulatory level in setting standards, in designing economic instruments and in plant sitting decisions; and that the polluter pays principle, which currently applies in the case of hydro, should also be applied in other power sector developments.